Stat3-mediated Th17 pathogenicity induced by periodontitis contributes to cognitive impairment by promoting microglial M1 polarization - Zhou, Yining; Xie, Xinyi; Chen, Huiwen; Xu, Lina; Qiu, Che; Shen, Hui; Zhou, Wei; Song, Zhongchen (Frontiers in Immunology, 2025)
IntroductionPeriodontitis has been identified as a potential risk factor for cognitive impairment associated with immune dysregulation. T helper 17 (Th17) cell-associated immune responses are involved in both diseases, while signal transducer and activator of transcription 3 (Stat3) is kown to be crucial for Th17 pathogenicity. Accordingly, in this study, we investigated how Stat3-mediated Th17 pathogenicity contributes to the link between periodontitis and cognitive impairment.MethodsLevels of Th17-related cytokines in gingival crevicular fluid (GCF) were measured in individuals with and without cognitive impairment. A periodontitis model was established in mice with conditional deletion of Stat3 in Th17 cells (Stat3fl/fl; Il17a-CreERT2, cKO) and wild type (Stat3fl/fl, WT) mice via injection of Porphyromonas gingivalis lipopolysaccharide (P. gingivalis LPS) into gingival sulcus. Cognitive function was assessed through behavioral tests. Expression of Th17-related cytokines and microglial pro-inflammatory markers was evaluated by reverse transcription-quantitative PCR (RT-qPCR), ELISA, flow cytometry, and immunohistochemistry. To evaluate effects of CD4+ T cells on microglial M1 polarization, BV2 microglia were co-cultured with primary CD4+T cells which were stimulated with P. gingivalis LPS after isolated from cKO and WT mice.ResultsCompared with cognitively normal participants, levels of Th17-related cytokines increased in participants with cognitive impairment. Significant alveolar bone resorption and cognitive impairment were observed in WT mice with periodontitis. These periodontitis-induced changes were alleviated in cKO mice, accompanied by a weakening of neuroinflammation and mitigation of Th17 immune responses. In vitro, M1 polarization and activation of the MAPK/ERK signaling pathway were inhibited in BV2 cells co-cultured with Stat3-deleted Th17 cells.ConclusionStat3-mediated Th17 pathogenicity bridged the correlation between periodontitis and neuroinflammation related to cognitive impairment, offering novel perspectives for a therapeutic target for blocking the mouth-to-brain axis.